2018
DOI: 10.1016/j.jhsa.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Local Bone Density in Early Thumb Carpometacarpal Joint Osteoarthritis

Abstract: Diagnostic II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…We found 22% lower HU in the trapezium in high grade osteoarthritis patients (HU mean 288) compared with low grade osteoarthritis (HU mean 369) in Schreiber et al [ 19 ]. The low grade osteoarthritis patients from Schreiber et al had 12% lower HU than control subjects, and our high grade osteoarthritis patients had 31% lower HU then control subjects from Schreiber et al [ 19 ]. However, a limitation may be that OA grading has low intra-rater and inter-rater reliability [ 20 ].…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…We found 22% lower HU in the trapezium in high grade osteoarthritis patients (HU mean 288) compared with low grade osteoarthritis (HU mean 369) in Schreiber et al [ 19 ]. The low grade osteoarthritis patients from Schreiber et al had 12% lower HU than control subjects, and our high grade osteoarthritis patients had 31% lower HU then control subjects from Schreiber et al [ 19 ]. However, a limitation may be that OA grading has low intra-rater and inter-rater reliability [ 20 ].…”
Section: Discussionmentioning
confidence: 46%
“…Where CT is already used as a pre-operative examination when treating comminuted distal radius fractures, HU may give an indication of the bone quality of the radius and be of value when deciding on the specific fracture treatment e.g., augmentation by external fixation. In a recent study, HU was used to examine bone quality in the trapezium and revealed that bone density of the proximal metacarpal bone and the trapezium was lower in patients with first grade osteoarthritis in the trapeziometacarpal joint as compared to patients with no osteoarthritis [ 19 ]. We found 22% lower HU in the trapezium in high grade osteoarthritis patients (HU mean 288) compared with low grade osteoarthritis (HU mean 369) in Schreiber et al [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the formation of bone redundancy was accompanied by a substantial bone loss in subchondral bone, with loss of normal bone structure in a rat OA model. Other partial findings also support the reduction of bone density in osteoarthritis (Schreiber et al, 2018;Muhlenfeld et al, 2021;Zhu Z. et al, 2021). A review in regard to the relationship between BMD and osteoarthritis of the knee by Choi et al (2021) showed that patients with moderate and severe OA had significantly lower BMD than the normal ones.…”
Section: The E Ects Of Irisin On Osteoarthritis Irisin and Bone Miner...mentioning
confidence: 76%
“…For both measurements, the points were first marked on the "PA" 3D view but subsequently adjusted while checking all around the 3D reconstruction image ensuring most accurate placement (►Figs. [1][2][3][4][5]. The same process was strictly followed for each specimen and performed by the first author.…”
Section: Methodsmentioning
confidence: 99%